2017
DOI: 10.2196/resprot.6792
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 16-Week Multimodal Exercise Program on Individuals With Dementia: Study Protocol for a Multicenter Randomized Controlled Trial

Abstract: BackgroundThe increasing prevalence of dementia in the next decades is accompanied by various societal and economic problems. Previous studies have suggested that physical activity positively affects motor and cognitive skills in individuals with dementia (IWD). However, there is insufficient evidence probably related to several methodological limitations. Moreover, to date adequate physical activity interventions specifically developed for IWD are lacking.ObjectiveThis study aims to investigate the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 80 publications
1
19
0
3
Order By: Relevance
“…A major strength of the expert panel was the comprehensive and thorough analysis of the appropriateness of motor assessments considering specific characteristics of IWD. Following the expert panel, the recommended assessments were applied in a trial of our own with IWD in mild to moderate stages of the disease [ 67 ] and demonstrated feasibility. This is in line with previous investigations successfully utilising these assessments or determining their reliability.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of the expert panel was the comprehensive and thorough analysis of the appropriateness of motor assessments considering specific characteristics of IWD. Following the expert panel, the recommended assessments were applied in a trial of our own with IWD in mild to moderate stages of the disease [ 67 ] and demonstrated feasibility. This is in line with previous investigations successfully utilising these assessments or determining their reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have studied the effects of different physical activities such as aerobic, cycling, and gait training with people with MCI, and in general, the results showed beneficial effects in maintaining both physical and cognitive capabilities [19,22]. While exercise is beneficial, age-related changes often result in decreased physical activity for older adults, particularly those with MCI where changes in cognition create additional challenges [5,15].…”
Section: Introductionmentioning
confidence: 99%
“…For this manuscript, we followed the guidelines and recommendations of the Consolidated Standards of Reporting Trials statements [ 51 , 52 ]. The reader is referred to the published study protocol for a detailed description of the study design and methods [ 53 ]. The following sections will only provide a brief summary of study methods.…”
Section: Methodsmentioning
confidence: 99%
“…This allocation ratio accounts for assumed higher dropout quotes and insufficient adherence to the MEP in the IG. The randomization was carried out separately for each of the 36 care facilities that served as recruitment sites, and minimization considered age, sex, Mini-Mental State Examination (MMSE) score and performance in the modified 30-s chair stand test (30s CST) of participants (for details please refer to our study protocol [ 53 ]). If possible, we blinded investigators who examined gait, motor, and cognitive performance to group allocation, i.e., the investigators did not know whether a participant was part of the IG or CG in order to ensure objectivity of testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation